2018
DOI: 10.3319/tao.2018.05.07.01
|View full text |Cite
|
Sign up to set email alerts
|

The Holocene paleo-environmental history of the Gangkou River estuary, Hengchun Peninsula, Taiwan

Abstract: The Taiwan coastal areas are facing predicted sea-level rise effects in the global climate change context. Better understanding of the mechanisms and forcing factors driving the geomorphological evolution of Taiwan's coastline is essential. We highlight the potential of small river estuaries as archives of coastal evolution and provide a paleo-environmental reconstruction of the Gangkou River estuary based on results from a combined methodological approach using geomorphological, sedimentological, and geochron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…7. From our field investigations, we found that the sediment underlying the coastal sand dunes is a mud layer dated to ~8 ka (Lüthgens et al 2018). The high river terrace on the right bank of the Gangkou River in the GY area was chosen for geological drilling.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…7. From our field investigations, we found that the sediment underlying the coastal sand dunes is a mud layer dated to ~8 ka (Lüthgens et al 2018). The high river terrace on the right bank of the Gangkou River in the GY area was chosen for geological drilling.…”
Section: Resultsmentioning
confidence: 99%
“…The river mouth is usually blocked by barriers, which typically produce a swath of relatively still water extending landward for several hundred meters to 1 km. It is worth mentioning that Lüthgens et al (2018) investigated the coastal landscape south of the Gangkou River mouth. They reported an ~8 ka estuarine muddy bed, showing that the river flowed ~600 m south of its present position or, more likely, formed an estuary at least 700 m wide (including the present river mouth), apparently caused by the Holocene sea level rise.…”
Section: Geomorphologic Featuresmentioning
confidence: 99%
See 3 more Smart Citations